La narrativa informacional del perfil de TikTok de @ecuavisaec – Quito – Ecuador. - De la Cruz Chicaiza, Jonathan Bladimir (2023)
This research report was carried out to demonstrate the evolution and information broadcast by @ecuavisaec's TikTok profile. The objective is to analyze the content and impact of Ecuavisa's TikTok application. The methodology of this study is quantitative and qualitative, with a technique of interviews and participant observation. For this report, personalized observation sheets with their respective characteristics were used, applied in the months of October to December 2022, these are complemented with an interview with the media's social media strategist. After having analyzed and discussed the results obtained, it is concluded that the informational narrative of this media is still not clear and is confused with the entertainment content that it offers to its audiences. In addition, an instructive triptych is presented as a proposed solution to the shortcomings that exist with its 7 steps to follow that seek to strengthen the professional work of the digital department of ecuavisa.com.